ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER LOYALTY AT E-COMMERCE SHOPEE IN THE COVID-19 PANDEMIC - Salamun, Suyono; Kurniastuti, Cahyani; Subaebasni, Subaebasni (Dinasti Publisher, 2021)
The purpose of this study is to analyze of the Influence of reliability, assurance, tangibles, empathy, and responsiveness on Customer Loyalty at E-commerce Shopee in the COVID-19 Pandemic. The research methodology is a quantitative method with cross-section data and primary data obtained from questionnaire distribution. Sampling technique using purposive sampling method with data in 2020. The data analysis technique is multiple linear regression by conducting validity test, reliability test, model stability test, linearity test, normality test, classical assumption test (multicollinearity test, heteroscedasticity test) and test of t-statistic hypothesis and f-statistic on test significance of impact together with 5% significance level The results of this study indicate in partial variables of reliability, assurance, tangibles, empathy, and responsiveness have a positive impact and significant on Customer Loyalty at E-Commerce Shopee. Meanwhile, the independent variables of reliability, assurance, tangibles, empathy, and responsiveness collectively have a significant relationship with the dependent variable of Costumer Loyalty at E-Commerce Shopee. The Coefficient of determination of this research equally to 84,42%, it means variation of the independent variables of reliability, assurance, tangibles, empathy, and responsiveness can explain the variations of the rise and fall of the dependent variable of Customer Loyalty on E-Commerce Shopee by 84,42%, while the rest of 15,58%, is influenced by other independent variables.